2006
DOI: 10.1097/01.blo.0000218736.23506.fe
|View full text |Cite
|
Sign up to set email alerts
|

Misuse of Baseline Comparison Tests and Subgroup Analyses in Surgical Trials

Abstract: It is unclear whether the misuse of statistical tests that compare patients' baseline characteristics and subgroup analyses in randomized controlled trials can be extrapolated to the surgical literature. We did an observational study evaluating the current use of baseline comparability tests and subgroup analyses in surgical randomized controlled trials. Published surgical randomized controlled trials in four medical journals were identified. We also identified randomized controlled trials in the Journal of Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…The fourth study found subgroup analyses reported in only seven RCTs, and no details had been included in the trial registry entries for six of these RCTs, while the seventh had no discrepancies [6]. In seven studies [11],[13],[18],[21],[22],[26],[30], where the comparison was mostly made between the methods and results sections of the trial publication, it was found that a number of subgroup analyses conducted were not pre-specified (range: 14% [8/58] to 91% [49/54] of RCTs), pre-specified, but not reported in the publication (range: 27% [3/11] to 53% [9/17]), or contained a mixture of pre-specified and non-pre-specified subgroup analyses (range: 10% [6/58] to 65% [135/207]).…”
Section: Resultsmentioning
confidence: 99%
“…The fourth study found subgroup analyses reported in only seven RCTs, and no details had been included in the trial registry entries for six of these RCTs, while the seventh had no discrepancies [6]. In seven studies [11],[13],[18],[21],[22],[26],[30], where the comparison was mostly made between the methods and results sections of the trial publication, it was found that a number of subgroup analyses conducted were not pre-specified (range: 14% [8/58] to 91% [49/54] of RCTs), pre-specified, but not reported in the publication (range: 27% [3/11] to 53% [9/17]), or contained a mixture of pre-specified and non-pre-specified subgroup analyses (range: 10% [6/58] to 65% [135/207]).…”
Section: Resultsmentioning
confidence: 99%
“…The findings of subgroup analyses offer the promise of individualising patient care, and such analyses are common in randomised controlled trials, with 40-65% reporting them. [1][2][3][4][5][6][7] In particular, claims of subgroup effect, in which the authors convey a conviction or belief of a difference in treatment effects between patient subgroups, can have a substantial impact on clinical practice and policy decision. One study found that in 35 randomised controlled trials published in top general medical journals reporting subgroup analyses, 21 (60%) claimed subgroup effects.…”
Section: Introductionmentioning
confidence: 99%
“…Such secondary subgroup analyses are common in randomized trials. A recent survey found that 38% (twenty-seven) of seventy-two surgical trials included subgroup analyses, and 57.4% (thirty-one) of fifty-four reported subgroup analyses claimed subgroup effects (that is, that the effect differed across subgroup categories) 3 . On the one hand, the real subgroup effects are important and informative, which allows targeting use of therapies to individual patients to achieve optimal treatments.…”
mentioning
confidence: 99%